Use of a Liquid Supplement Containing 2 Human Milk Oligosaccharides: The First Double-Blind, Randomized, Controlled Trial in Pre-term Infants - Hascoët, Jean-Michel; Chevallier, Marie; Gire, Catherine; Brat, Roselyne; Rozé, Jean-Christophe; Norbert, Karine; Chen, Yipu; Hartweg, Mickaël; Billeaud, Claude (Frontiers in Pediatrics, 2022)
There is growing evidence supporting the benefit of human milk oligosaccharides (HMOs) on reducing risk of illnesses and improving immune function in newborn infants, but evidence in pre-term infants is lacking. This randomized, double-blind, placebo-controlled trial (NCT03607942) of pre-term infants evaluated the effects of HMO supplementation on feeding tolerance, growth, and safety in 7 neonatal units in France. Pre-term infants (27–33 weeks' gestation, birth weight <1,700 g) were randomized early after birth to receive HMO supplement (n = 43) [2′-fucosyllactose (2′FL) and lacto-N-neotetraose (LNnT) in a 10:1 ratio (0.374 g/kg body weight/day)] or an isocaloric placebo (n = 43) consisting of only glucose (0.140 g/kg/day) until discharge from the neonatal unit. Anthropometric z-scores were calculated using Fenton growth standards. Primary outcome was feeding tolerance, measured by non-inferiority (NI) in days to reach full enteral feeding (FEF) from birth in HMO vs. placebo group (NI margin = 4+ days). Mean number of days on intervention prior to FEF was 8.9 and 10.3 days in HMO and placebo, respectively. Non-inferiority in time to reach FEF in HMO (vs. placebo) was achieved [LS mean difference (95% CI) = −2.16 (−5.33, 1.00); upper bound of 95% CI < NI margin] in full analysis set and similar for per protocol. Adjusted mean time to reach FEF from birth was 2 days shorter in HMO (12.2) vs. placebo (14.3), although not statistically significant (p = 0.177). There was no difference in weight-for-age z-scores between groups throughout the FEF period until discharge. Length-for-age z-scores were higher in HMO at FEF day 14 [0.29 (0.02, 0.56), p = 0.037] and 21 [0.31 (0.02, 0.61), p = 0.037]. Head circumference-for-age z-score was higher in HMO vs. placebo at discharge [0.42 (0.12, 0.71), p = 0.007]. Occurrence of adverse events (AEs) was similar in both groups and relatively common in this population, whereas 2.3 and 14.3%, respectively, experienced investigator-confirmed, related AEs. HMO supplementation is safe and well-tolerated in pre-term infants. After 9 days of supplementation, the HMO group reached FEF 2 days earlier vs. placebo, although the difference was not statistically significant. In addition, HMO supplementation supports early postnatal growth, which may have a positive impact on long-term growth and developmental outcomes.